Optical properties and morphology analysis of hexagonal WO3 thin films obtained by electron beam evaporation - Shakoury, Reza; Arman, Ali; Rezaee, Sahar; Korpi, Alireza Grayeli; Kulesza, Sławomir; Luna, Carlos; Bramowicz, Mirosław; Mardani, Mohsen (Journal of materials science. Materials in electronics, 2021)
WO 3 films with thicknesses between 550 and 853 nm were deposited on glass substrates using the electron beam evaporation method at room temperature. The microstructures and surface roughness of the films were studied by X-ray diffraction (XRD) and atomic force microscopy (AFM). It was observed that the crystalline structure of the WO 3 thin films significantly changes from the amorphous to crystalline states with a crystalline texture, and the mosaicity and grain size dependent on the film thickness. The transmittance spectra of the obtained WO 3 films were measured in the range from 340 to 850 nm, and the Swanepoel method was used to determine the refractive indices and the thicknesses of the WO 3 films. The obtained optical functions reveal the highly homogeneous structure of the films.